Analysis of the determinants of foreign direct investment in the Arab States Using the principal component analysis method - Sahel, Mohamed; Bentafet, Adbelhak (Finance and Business Economies Review, 2019)
The present study aims to analyze the determinants of FDI in the Arab countries. Therefore, the method of principal component analysis has been used as the basis of the analyses. The results revealed a positive correlation between each of the parameters of the study, i.e., the independent variables studied, namely gross domestic product (GDP), the size of the population as two measures to measure the size of the domestic market, inflation, open trade ; and the dependent variable of the study which is foreign direct investment in Arab states in 2017. The study recommended that policies should be directed towards increasing trade openness to promote FDI flows to Arab countries